FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENDERITA DIABETES MELLITUS DALAM MENJALANKAN DIIT - Dwi Nur Aini; Arifianto -; Bagus Prasetia (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background:Diabetes Mellitus (DM) is one among the chronic diseases that will be increase the number of sufferer in the future. Diabetes is one also of the diseases that endanger the human health. The purpose of this research is to identify the factors which related to compliance of patiens with diabetes mellitus to commit the DIIT.Method: This research method using quantitative research with cross sectional approach. The population of this study is 68 people. This sampling technique using total sampling as much as 68 people. The data obtained using a quesionnaire, the statistical test used spearman rank test.Results: Based of spearman rank test, the result obtained for age p value 0,336 (pvalue> 0.05), then there is no relationship beetween age and compliance self motivation p value = 0,000(pvalue< 0,05), diit understanding p value = 0,000 (pvalue< 0,05), family support p value = 0,000 (pvalue< 0,05) then there is a relationship beetween self motivation, diit understanding, and family support with compliance.Conclusion: This research can be concluded there was no relationship beetween age with the commit and there is a relationship beetween self motivation, diit understanding, and fammilies support with compliance to commit the DIIT. Keywords : Age, Self motivation, Understanding, Family support, Commit